The shared genetic architecture between epidemiological and behavioral traits with lung cancer - Rowland W. Pettit (Nature Portfolio, 2021)
Abstract The complex polygenic nature of lung cancer is not fully characterized. Our study seeks to identify novel phenotypes associated with lung cancer using cross-trait linkage disequilibrium score regression (LDSR). We measured pairwise genetic correlation (rg) and SNP heritability (h2) between 347 traits and lung cancer risk using genome-wide association study summary statistics from the UKBB and OncoArray consortium. Further, we conducted analysis after removing genomic regions previously associated with smoking behaviors to mitigate potential confounding effects. We found significant negative genetic correlations between lung cancer risk and dietary behaviors, fitness metrics, educational attainment, and other psychosocial traits. Alcohol taken with meals (rg = − 0.41, h2 = 0.10, p = 1.33 × 10–16), increased fluid intelligence scores (rg = − 0.25, h2 = 0.22, p = 4.54 × 10–8), and the age at which full time education was completed (rg = − 0.45, h2 = 0.11, p = 1.24 × 10–20) demonstrated negative genetic correlation with lung cancer susceptibility. The body mass index was positively correlated with lung cancer risk (rg = 0.20, h2 = 0.25, p = 2.61 × 10–9). This analysis reveals shared genetic architecture between several traits and lung cancer predisposition. Future work should test for causal relationships and investigate common underlying genetic mechanisms across these genetically correlated traits.